TEACHERS’ STRATEGIES AND CHALLENGES IN TEACHING SPEAKING TO YOUNG LEARNERS - Indra Sudrajat (English Education Department of STKIP Pasundan, 2022)
The purpose of this study was to find out the teacher's reflection on the strategies used, to find out the challenges and how the teacher overcomes the challenges faced when teaching English to young learners. To be able to achieve a learning goal, teaching English speaking to young learners must be effective and interesting. But in fact, teaching speaking to young learners is a skill that is quite difficult for EFL teachers to teach. Therefore, this study tries to find out the strategies used by teachers, the challenges faced, and how to deal with these challenges. The research method in this research is a qualitative descriptive method. Data were obtained from three English teachers in a kindergarten in Bandung. The instruments used to collect data were close-ended questionnaires and semi-structured interviews which were transcribed descriptively. In addition, the data analysis used is data reduction, data display, and conclusions. The results of the research showed that the teacher used three strategies to teach English speaking in young learners' classes including drilling, games, and songs. Meanwhile, the researcher reveals the research findings related to the challenges faced by teachers are divided into two, namely; internal and external challenges. Internal challenges include the mother tongue which is still a challenge for students and the lack of vocabulary. External challenges include a lack of exposure to English outside the classroom. To overcome these challenges, teachers must apply different teaching strategies, provide opportunities for students to speak English in the classroom, adequate learning facilities, classroom management, create a pleasant classroom atmosphere, and do self-reflection.